Security for personal health records occupying terabytes using cryptography and encoder decoder - Sankaran, Sathya; Rajasekaran, Rajkumar (International Journal of Engineering and Technology, 2019)
Personal Health Records may contain personal data along with medical data that is available in Electronic Health Records. This research proposes an encryption decryption method with encoder decoder for records in well established hospitals that store medical records in terms of terabytes. For encryption, the medical information including images is converted into binary. This is sent to an encoder and the information is stored in chunks to form a matrix. Then it undergoes matrix transformation and split into sub matrices. This is sent to the destination. The reverse is done in the decryption module. Cryptanalysis for the algorithm used and brute force attack is almost impossible or takes a number of years. A comparative study of the proposed algorithm is done with DES, AES, IDEA and BLOWFISH and it is realized the proposed algorithm is immune to cryptanalysis methods to which the compared algorithms are not. The personal health records are located in the cloud. The encryption decryption provides data security which is used to provide cloud security.